2014
DOI: 10.1007/s13277-014-2618-1
|View full text |Cite
|
Sign up to set email alerts
|

Activating transcription factor 3 interferes with p21 activation in histone deacetylase inhibitor-induced growth inhibition of epidermoid carcinoma cells

Abstract: Inhibition of histone deacetylase (HDAC) activity by HDAC inhibitors (HDACis) results in cancer cell growth inhibition, and HDACis have been revealed as potential anti-skin cancer agents. p21 is a cyclin-dependent kinase inhibitor and an essential regulator of growth inhibition. Recently, we reported that activating transcription factor 3 (ATF3) could significantly promote skin cancer cell growth. This study explored the relationship between ATF3 and HDACi-induced growth inhibition of epidermoid carcinoma cell… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
1
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 31 publications
2
1
0
1
Order By: Relevance
“…G 2 -M arrest and the resistance of noncancerous cells to HDACi have been described previously (45) and reflect the presence of a G 2 checkpoint in normal cells, which is absent in the majority of cancer cells; abolishing the G 2 checkpoint using checkpoint kinase 1 abrogates this resistance (46). Our findings in bladder cancer that the reactivation of p21 is in parallel to the reactivation of ATF3 are in contrast to the observation made in epidermoid carcinoma, where ATF3 acts as an oncogenic activator (47).…”
Section: Discussionsupporting
confidence: 76%
“…G 2 -M arrest and the resistance of noncancerous cells to HDACi have been described previously (45) and reflect the presence of a G 2 checkpoint in normal cells, which is absent in the majority of cancer cells; abolishing the G 2 checkpoint using checkpoint kinase 1 abrogates this resistance (46). Our findings in bladder cancer that the reactivation of p21 is in parallel to the reactivation of ATF3 are in contrast to the observation made in epidermoid carcinoma, where ATF3 acts as an oncogenic activator (47).…”
Section: Discussionsupporting
confidence: 76%
“…In general, the p21 gene is regulated in a p53-dependent or/and p53-independent manner [38]. A recent study showed that TSA induces p21 expression via the down-regulation of ATF3 in A431 epidermoid carcinoma cells [30]. In HeLa cells, we observed similar effects of TSA on p21 and ATF3, whereas the other tested HDACIs induced both p21 and ATF3 expressions.…”
Section: Discussionsupporting
confidence: 59%
“…These findings can be attributed to BM-MSCs' potential to ameliorate apoptosis inducers, either hyperglycemia or oxidative stress or beta-cell inflammatory environment or ER stress according to the result of the present work that reduced further renal tissue damage and apoptosis (Bugliani et al, 2019). In addition, these findings could be reverted to the elevated expression of activated transcription factor 3 (ATF3) that inhibits apoptosis via downregulating the expression of proapoptotic factor P21 (Hao et al, 2014) on the other hand. Altogether, BM-MSCs could ameliorate beta cell apoptosis in a molecular pathway (ATF3+/P21-/FAS-/FAS L -/BAX -/caspase-3-/ P53-/BCL2+) or (insulin+/hyperglycemia-/redox-/ER stress-/inflammatory cytokines-/FAS-/FAS L -/BAX -/caspase-3-/ P53-/BCL2+).…”
Section: Discussionmentioning
confidence: 65%